Asuhan Keperawatan Gerontik Pada Pasien Dengan Dermatitis Di Panti Sosial Tresna Werdha Sabai Nan Aluih Sicincin Kabupaten Padang Pariaman - Marisa Musfo Yolanda; Sandra Dewi; Hasmita .; Kheniva Diah Anggia (CV. ITTC INDONESIA, 2026)
Based on data from the World Health Organization (2020), contact dermatitis ranks second, around 14-20%. The prevalence of contact dermatitis in Indonesia reaches 36.4%. The number of dermatitis in West Sumatra is 9.2% and in Padang City in 2020 it was ranked first with 15,556 cases. During the preliminary study at the Sabai Nan Aluih Sicincin PSTW, 5 patients with dermatitis were found. The purpose of this study is to describe nursing care for the elderly with dermatitis at the Sabai Nan Aluih Sicincin PSTW. Dermatitis in the elderly is often caused by skin changes due to aging, chemical exposure, and infection. The research method used was a case study with 1 client as a sample. The study was conducted in Gunung Tigo village through interviews, observations, and physical examinations on clients at PSTW Sabai Nan Aluih Sicincin on February 18-23, 2026. The results of the assessment were Mr. I, aged 70 years, the client said itching on the right ankle, the back of the left and right feet. The nursing diagnoses found were impaired skin integrity, impaired sense of comfort, and risk of infection. Interventions provided included skin care, maintaining hygiene, and administering topical medications such as salaf. After the intervention for 5 days, the results showed a decrease in itching in the client. It is hoped that the client can treat the disease independently and maintain hygiene and caregivers are expected to continue and monitor client care regularly, provide assistance, and immediately report to the leader if there is a decline in the client's health condition for further treatment.